Phthalate metabolite mixtures and dose-response associations with depressive symptoms in U.S. adults - Penghui Li; Huimin Zhang; Yike Han; Shuo Xie; Wanning Li; Liyun Kong; Yue Zhang (Ecotoxicology and Environmental Safety)
Depression is a significant global health challenge. Emerging evidence links phthalate exposure to depressive symptoms, but population-based data are limited. This study aims to examine the impact of Mono-Phthalate Acid Esters (mPAEs) exposure on depressive symptoms in a general adult population and to characterize the dose-response relationship between urinary mPAEs and depressive symptoms. Data from the National Health and Nutrition Examination Survey (NHANES, 2005–2018) were used. A total of 9618 participants aged≥ 20 years were analyzed for 11 phthalate metabolites and depressive symptoms assessed via the Patient Health Questionnaire-9 (PHQ-9). Logistic regression, weighted quantile sum (WQS) regression, and quantile g-computation (QGC) models were employed to evaluate individual and mixture effects. The study identified significant associations between exposure to specific phthalate metabolites (MnBP, MiBP, MBzP, MEHHP, MECPP, BBP) and depressive symptoms in adults. Logistic regression showed that higher urinary concentrations of these metabolites were linked to increased depressive risk: compared to the lowest quartile (Q1), the highest quartile (Q4) had 50 %–88 % higher risk, with corresponding odds ratios (ORs) ranging from 1.50 (95 % CI: 1.19–1.89, P = 0.001) for MnBP to 1.88 (95 % CI: 1.53–2.31, P < 0.001) for MBzP. Trend tests confirmed significant linear relationships (all P-trend <0.05). Dose-response analysis using restricted cubic spline (RCS) revealed significant linear relationships for MnBP, MiBP, MBzP, and BBP (Poverall<0.05, Plinear <0.05), with no significant non-linear associations (Pnonlinear >0.05). Combined exposure analyses showed that MnBP, MBzP, and MEHHP contributed most to depressive symptoms risk: the WQS model indicated a significant positive overall effect of the mPAEs mixture (OR=1.23, 95 % CI: 1.08–1.41, P < 0.01), while the QGC model showed that each interquartile increase in the mixture was associated with an 18 % higher risk (OR=1.18, 95 % CI: 1.02–1.36, P < 0.05). Subgroup analyses indicated stronger associations among females and older adults (interaction P < 0.05 for gender and age). These findings underscore the adverse neuropsychiatric effects of PAEs exposure, emphasizing the need for safer alternatives to reduce population-level depressive symptoms risk. Further longitudinal studies are warranted to confirm causality and elucidate underlying mechanisms.